(untitled) (Journal of Veterinary Medicine and Animal Production, 2023)
The study aimed to evaluate the effect of subcutaneous injection of a solution contains calcium gluconate, magnesium hypophosphite and glucose into cross-bred dairy cows during the early postpartum period (PPP) on the rates of the first service non-return (FSN) and repeat breeding (RB). A total of 150 cows were selected randomly and divided into treated cows (no. = 90); these were the cows that were subcutaneously injected with 100 ml of the solution, and untreated cows (no = 60); these were the control cows that were not injected with the solution. Based on the number of parities, treated and untreated cows were further subdivided into primiparous and multiparous cows to compose four experimental sub-groups: treated primiparous (no. = 15 cows), treated multiparous (no. = 75), untreated primiparous (no. = 10 cows) and untreated multiparous (no. = 50 cows). The duration of postpartum period (PPP), the days open (DO), the number of services per conception (NSP), the rates of the FSN and RB were determined for each sub-group. The results revealed significantly (P <0.0001) shorter PPP, DO and NSC, in treated multiparous and untreated primiparous cows compared to cows in the two other sub-groups. The rate of the FSN was higher (70.0%) in untreated primiparous cows and treated multiparous cows (64.0%) than the rates (16.0%) of this trait in untreated multiparous cows and treated primiparous cows (6.6%). The rates of RB were lower (0.0%) in untreated primiparous cows and treated multiparous cows (13.3%) than the rates in treated primiparopus cows (40.0%) and untreated multiparous cows (42.0%). The study concluded that subcutaneous injection of 100 ml of a solution contains calcium gluconate, magnesium hypophosphite and glucose during the early postpartum period could elevate the rate of the FSN and alleviate the rate of RB in multiparous cross-bred dairy cows, however; this treatment protocol had worsened the reproductive performance of primiparous cows. Further studies to measure the blood levels of calcium, phosphorous, magnesium, glucose and other blood constituents related to fertility after postpartum subcutaneous injection of a solution contains calcium gluconate, magnesium hypophosphite and glucose are recommended